Strangeness Suppression and Recombination Effect in Large Transverse Momentum Dependent Quark Statistics - Liang, Thow Yick (Institutional Knowledge at Singapore Management University, 1985)
The quark statistics has successfully described the variation of the ratios ?±/p, K±/p and $$p/\bar p$$ with energy purely statistically and the variation of ?-/?+, K?/K+ and $$p/\bar p$$ with largep T by means of the leading-quark effect. This model is now further enhanced by thep T-dependent strangeness suppression mechanism and recombination effect, so that the characteristics exhibited by the ratios K+/?+, K-/?-, ?/?-, p/?+ and $$\bar p/\pi ^ - $$ could be studied phenomenologically.